The application value of the detection of the level of tissue polypeptide antigen, ovarian cancer antigen X1, cathepsin L and CA125 on the diagnosis of epithelial ovarian cancer - Lv, X-L; Zhu, Y; Liu, J-W; Ai, H (European review for medical and pharmacological sciences, 2016)
We investigated the value of the joint detection of tissue polypeptide antigen (TPA), ovarian cancer antigen X1 (OVX1), cathepsin L (CTSL) and CA125 on the early diagnosis of epithelial ovarian carcinoma (EOC). From October 2011 to February 2015, 84 cases of patients under surgical treatment of epithelial ovarian cancer, 98 cases of patients with benign epithelial ovarian tumor and 51 subjects in healthy control group were selected to detect the level of TPA, OVX1 and CTSL in serum from the Obstetrics and Gynecology Department of the First Affiliated Hospital of Liaoning Medical University. The clinical data of patients with ovarian tumor were collected and analyzed, and the levels of CA12 were measured. 3 indicators in the malignant group were significantly higher than those in the benign group and healthy control group (p < 0.05). The total positive rate and the positive rate of early detection of TPA on EOC were the highest, and the total positive rate of OVX1 was lower than that of CA125. The total positive rate and the positive rate of early detection of CA125+TPA on EOC were the highest. The positive rate of early detection and the total positive rate of the pairwise combined detection of the other index and CA125 on EOC were significantly higher than those of the single detection of CA125 (p < 0.05). The joint detection of CA125+ OVX1 and the single detection of CA125 were not statistically significant. However, the remaining differences were statistically significant (p < 0.05). The level of TPA, OVX1 and CTSL in serum was potential detection index, the joint detection of TPA and CA125 was the ideal combination, which took into account the total positive rate, the positive rate of early detection on EOC and the improved diagnostic rate of EOC.